Measurement of alpha-amylase activity in cat plasma test of specificity of a chromogenic substrate, reference values - Ouedraogo, G. (Veterinary clinical pathology, 1992)
Glucoamylase activity can interfere with the measurement of alpha-amylase activity in cat plasma. This can be avoided by the use of "blocked" substrates such as 4,6-O-benzylidene-4-nitrophenyl-alpha-D-maltoheptaoside. In 241 healthy cats, reference values were 586 +/- 241 U/L (m +/- standard deviation) at 30 degrees C; age, sex, overnight fasting, and mild hemolysis had no significant effect